Population Estimation and Habitat Preference of Coconut Crab (Birgus latro L.) on Bakalan Island, Banggai Archipelago, Central Sulawesi - Salanggon, Rinaldi; Tadeko , Fazlur Rahman I; Annawaty (BIOEDUSCIENCE, 2026)
Background: Write The coconut crab (Birgus latro Linnaeus, 1767) is the largest terrestrial crustacean and is currently classified as Vulnerable by the IUCN. Although its distribution in Central Sulawesi has been documented, information on population size and habitat preferences remains limited for many islands within its range. This study aimed to estimate the population size of B. latro on Bakalan Island, Banggai Archipelago, Indonesia and to identify its preferred habitats. Methods: Field surveys were conducted from November to December 2023 at five sampling stations on Bakalan Island. Coconut crabs were surveyed at night using baited plots established in representative habitat types, including rocky coastal areas, tree-root zones, and coconut plantations. Results: A total of 42 individuals were recorded during the survey. The population size of Birgus latro on Bakalan Island is estimated at 46,950 individuals, corresponding to a population density of 0.00112 individuals/m². The species was most frequently encountered in habitats characterized by rock crevices, tree-root systems, coconut trees (Cocos nucifera), coastal pandanus (Pandanus tectorius), Terminalia catappa, and shrub vegetation. Environmental conditions across sampling stations ranged from 26–31.1°C. Conclusions: Bakalan Island supports an important population of B. latro associated with a variety of coastal habitats that provide shelter and food resources. Given the species’ Vulnerable conservation status and ongoing habitat disturbance on small islands, the protection of key habitats is essential for the long-term conservation of coconut crab populations in the Banggai Archipelago.